Dian Sastrowardjojo Sebagai Citra Produk Untuk Iklan Kartu Perdana Mentari Free Talk di Surat Kabar - Aryanto, Hendro (Institute of Research and Community Outreach - Petra Christian University, 2010)
Advertisements do not just sell goods or services, but also reflect certain cultural aspects to their viewers because they attempt to change people’s lifestyles. Ads simplify lives, therefore do not see other factors that can contribute to happiness in life. The visualization for Mentari Free Talk SIM card advertisement shows the presence of social codes phenomenon that take on the gender perspective through the figure Dian Sastro, which are beauty, intelligence, and an artist who’s gaining popularity. Woman in this case becomes a means to identify a product in its ability in creating visibility or product image.